When Should the People Decide? Public Support for Direct Democracy in Australia. Issue 4 (10th August 2020) - Kildea, Paul; Brown, A J; Deem, Jacob
Abstract: This article examines the strength of support for direct democracy among Australian citizens, both in general and, in a world-first, across different specific topics. Analysing data from the Australian Constitutional Values Survey, we investigate whether that support is higher among people who are more educated and politically interested (in line with a 'cognitive mobilisation' hypothesis) or those who are dissatisfied with politics, with low levels of political trust ('political disaffection'). The article finds that Australians widely support the use of direct democracy, but especially with respect to constitutional issues and matters of principle that they feel they can readily engage with, whereas parliaments are still seen as best placed to decide more technical matters. The article also finds that support for direct democracy is strongest among politically disaffected citizens, in ways that suggest greater use of direct democracy may have a role to play in addressing decline in political trust in Australia.